Biomarker correlaton between shale, limestone, and sandstone of Yolde formaton, Northern Benue Trough (Journal of Pure and Applied Sciences (Science Forum), 2025)
The Yolde shales, limestone, and sandstone in the Gongola Sub-Basin, Northern BenueTrough, Nigeria, were both studied in the field and laboratory using the gas chromatog-raphy-mass spectrometry to expand our knowledge on their origin, relationship, thermalmaturities, and paleo-depositional environment. Results obtained from the field studiessuggest that the Yolde Formation was deposited between the marine and continental set-tings. Other properties of the transitional environment observed include bioturbation, highfossil content, cross beddings, and evidence of mud crack. Results from the laboratory anal-ysis obtained show that the studied oils are all related and believed to have been sourcedfrom a common petroleum source rock within the studied basin. The total ion current ofthe oils studied shows the presence of an unresolved complex mixture consistent with oilsthat have undergone biodegradation. This is because all the studied oils were extractedfrom outcrop samples. Trisnorhopanes thermal indicators of the studied oils are observedto fluctuate between 1.08 to 1.7 consistent with oil formed from petroleum source rocksthat are in the oil window. Equivalent vitrinite reflectance for the studied samples variesroughly from 0.88 to 1 which infers oils generated from rocks within the oil window. This isconsistent with the cross plot of sterane ratio C29 20S/ (20S + 20R) versus C32 homohopaneratio (22S/22S + 22R), which also confirms that the studied oils are thermally matured andvery close to the peak of oil generation. Cross-plot of n-alkanes/ isoprenoids shows thedominance of organic matter that originated from marine and then mixed environments.The Yolde Formation is known to have a maximum burial depth beyond 2,000 m in someparts of the Northern Benue Trough. This is therefore expected to find non-degraded oilsassociated with the deeply buried Yolde Formation.